DESCRIPTION OF STUDENT BEHAVIOR IN PREVENTING ANEMIA AT NURSING FACULTY UNIVERSITY OF PADJADJARAN - Juliana Chandra Purnama; Valentina B.M. Lumbantobing; Lilis Mamuroh (UPT Penerbitan Universitas Jember, 2020)
Background: Anemia is still a global health problem that occurs in several developing countries especially in adolescents. Anemia in adolescents is influenced by behavior in preventing anemia that does not pay attention to the adequacy of iron that the body needs. Purpose: This study aims to identify the description of student behavior in preventing anemia at Nursing Faculty University of Padjadjaran. Methods: The study population was students of the Faculty of Nursing Unpad Garut Campus with a total sampling technique of 291 respondents. The research instrument was an anemia prevention behavior questionnaire with a Likert scale of 18 statements. Data analysis used univariate analysis in the form of percentages and the results of the study consisted of good behavior and poor behavior categories. Results: The results showed that 158 ​​respondents (54.3%) had poor behavior in preventing anemia and 133 respondents (45.7%) had good behavior. As many as 18 statements in the anemia prevention behavior questionnaire, it is known that 84.2% of respondents chose the answer never to do the habit of consuming blood added tablets along with papaya / banana. Conclusion: Anemia prevention behavior in students of the Faculty of Nursing that is still not good can lead to anemia which will have an impact on student productivity so it is recommended that students increase their nutritional intake and avoid bad behavior that leads to anemia and can check hemoglobin levels to detect earlier if anemia occurs. Keywords: Students; Prevention of Anemia; Behavior